The chamber music of Hendrik Hofmeyr: an investigation and stylistic analysis of selected works - Carter, Justin (College of Music, 2019)
Hendrik Hofmeyr, professor and head of composition at the South African College of Music at the University of Cape Town, is probably the most performed and commissioned composer living in South Africa today. Chamber music forms an integral part of Hofmeyr’s musical output. The overwhelming majority of these works have been produced in the last ten years, demonstrating his growing interest in this genre of music. Furthermore, this demonstrates musicians’ increasing desire for Hofmeyr to compose more chamber works, as most of these compositions are commissions or requests, intended to be premiered and played by specific artists or ensembles. His chamber works already include seven duo sonatas, two trios with piano, two string quartets and a clarinet quintet, among many other lesser works. Indeed, of his roughly 190 numbered compositions, at least 29 are original chamber works (15% of the total). These are also supplemented with several important arrangements within the genre. With this in mind, the research presented here aims to explore each of these major chamber works, contextualise them, as well as examine them from their points of origin, their stylistic conception and musical characterisation. This analysis should provide useful insights into the compositional style of this South African composer. The guidelines of stylistic analysis presented by Jan LaRue form the inspiration for the analytical approach to be taken.1 Up to this point, there has been little discourse, especially in terms of analysis or comprehensive research, which has focussed on any of the chamber works by Hofmeyr. As such this research hopes to break new ground by investigating this important portion of his oeuvre, while at the same time bringing insights and reflections upon these pieces from the composer’s points of view, and then analysing and commenting on the formal structure, harmonic language, melodic writing and musical detail they contain as well as the sound world they create. Ultimately, by comprehensively examining Hofmeyr’s chamber music, and by keeping in mind the historical context, this aspiringly ground-breaking discussion looks towards highlighting what amounts to a much under-valued body of work within South African music.